Broken stent of endoscopic retrograde cholangiopancreatography mimicking a common bile duct stone: a case report - Nelson, Thirugnanasambandam; Pranavi, AmudaRavichandar; Sureshkumar, Sathasivam; Sreenath, GubbiShamanna; Ramesh, Ananthakrishnan; Bharathi, Deepak; Kate, Vikram (International Journal of Research in Medical Sciences, 2019)
Long standing biliary stent for biliary stricture may have complications like cholangitis, cholecystitis, stent fracture and stent migration. Treatment includes re-do endoscopic retrograde cholangiopancreatography, removal of fractured stent and restenting. Authors report a case of fractured biliary stent mimicking as distal common bile duct stone. Patient presented with features of cholangitis with history of endoscopic stenting 6 years back but lost follow up thereafter. Ultrasound showed 2cm calculus in distal common bile duct and the stent was seen on endoscopy through the papilla in the duodenum. Contrast enhanced computed tomography of abdomen showed radio opaque dense shadow in the distal common bile duct suggesting possibility of broken biliary stent. Redo endoscopic retrograde cholangiopancreatography failed to remove the fractured stent. A new stent was placed without complications. Patient underwent open common bile duct exploration and the fractured stent was removed. Patient recovered completely after the procedure.